Characterization of sources of aerosol particles affecting the Swedish air quality - Kristensson, Adam ; 0000-0002-0443-0564 (2003)
[abstract missing]
The information about affiliations in this record was updated in December 2015. The record was previously connected to the following departments: Department of Physics (011013000), Nuclear Physics (Faculty of Technology) (011013007)
Keywords: Fysicumarkivet A:000